Identification of Aflatoxigenic Fungi in Myristica fragrans using V8 and CAM Media - Arifah, Fitri; Aini, Luqman Qurata; Muhibuddin, Anton; Dianti, Sylvia; Prabowo, Matheus Randy (Research Journal of Life Science, 2022)
Nutmeg is a spice that might be susceptible to being infected with aflatoxigenic fungi. Aflatoxins are mycotoxins synthesized by certain strains of Aspergillus section Flavi. However, not all strains are able to produce aflatoxins. The approach frequently employed for this survey comprises the cultivation of strains in a suitable liquid or solid medium and their subsequent extraction and analysis for the presence of aflatoxins. To date, very few studies have been conducted on the identification of contaminate and aflatoxigenic fungi in Myristica fragrans. Therefore, this study aimed to identify the contaminate and aflatoxigenic fungi in Myristica fragrans growing on V8 and CAM Media. Isolation of the fungus was carried out by direct agar plating. Lasiodiplodia theobromae, Aspergillus niger, A. tamarii, Penicillium citrinum, Rhizopus delemar, A. nomiae, and A. aflatoxiformans were recovered from nutmeg kernels sampled from North Minahasa, North Sulawesi, Indonesia. The findings of fungal isolation demonstrated that L. theobromae was the most prevalent form of fungus detected in the nutmeg kernels (50%), followed by A. niger (38.13%) and A. tamarii (10%). A. nomiae and A. aflatoxiformans were the aflatoxigenic fungi isolated from M. fragrans kernels.